The single nucleotide beta-arrestin2 variant, A248T, resembles dynamical properties of activated arrestin - Şensoy, Özge (TUBITAK Scientific & Technical Research Council Turkey, 2020)
beta-arrestins are responsible for termination of G protein-coupled receptor (GPCR)-mediated signaling. Association of single nucleotide variants with onset of crucial diseases has made this protein family hot targets in the field of GPCR-mediated pharmacology. However, impact of these mutations on function of these variants has remained elusive. In this study, structural and dynamical properties of one of beta-arrestin2 (arrestin 3) variants, A248T, which has been identified in some cancer tissue samples, were investigated via molecular dynamics simulations. The results showed that the variant underwent structural rearrangements which are seen in crystal structures of active arrestin. Specifically, the "short helix" unravels and the "gate loop" swings forward as seen in crystal structures of receptor-bound and GPCR phosphopeptide-bound arrestin. Moreover, the "finger loop" samples upward position in the variant. Importantly, these regions harbor crucial residues that are involved in receptor binding interfaces. Cumulatively, these local structural rearrangements help the variant adopt active-like domain angle without perturbing the "polar core". Considering that phosphorylation of the receptor is required for activation of arrestin, A248T might serve as a model system to understand phosphorylation-independent activation mechanism, thus enabling modulation of function of arrestin variants which are activated independent of receptor phosphorylation as seen in cancer.
Keywords: Arrestin; G Protein-Coupled Receptor; Phosphorylation-Independent Activation; Cancer; Single Nucleotide Polymorphism; Molecular Dynamics Simulation